1999
DOI: 10.1038/45822
|View full text |Cite
|
Sign up to set email alerts
|

EPS8 and E3B1 transduce signals from Ras to Rac

Abstract: The small guanine nucleotide (GTP)-binding protein Rac regulates mitogen-induced cytoskeletal changes and c-Jun amino-terminal kinase (JNK), and its activity is required for Ras-mediated cell transformation. Epistatic analysis placed Rac as a key downstream target in Ras signalling; however, the biochemical mechanism regulating the cross-talk among these small GTP-binding proteins remains to be elucidated. Eps8 (relative molecular mass 97,000) is a substrate of receptors with tyrosine kinase activity which bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
367
3
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(384 citation statements)
references
References 19 publications
10
367
3
4
Order By: Relevance
“…It was previously shown that microinjection of active Ras in Swiss 3T3 cells and other cell types mimics the effect of active Rac on the actin cytoskeleton (56), which led to the idea that Ras is located upstream of Rac. In support for this notion, a recent study (62) demonstrated that the Ras-GEF, Sos-1, mediates PDGF-induced Rac activation downstream of Ras by forming a complex with two other proteins. However, the present observations in CHO cells indicate that Rac is not always located downstream of Ras, in a linear fashion, suggesting that more than a single mechanism for chemoattractant-induced Rac activation are operative.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It was previously shown that microinjection of active Ras in Swiss 3T3 cells and other cell types mimics the effect of active Rac on the actin cytoskeleton (56), which led to the idea that Ras is located upstream of Rac. In support for this notion, a recent study (62) demonstrated that the Ras-GEF, Sos-1, mediates PDGF-induced Rac activation downstream of Ras by forming a complex with two other proteins. However, the present observations in CHO cells indicate that Rac is not always located downstream of Ras, in a linear fashion, suggesting that more than a single mechanism for chemoattractant-induced Rac activation are operative.…”
Section: Discussionmentioning
confidence: 73%
“…The supernatants were used as cell extracts. The glutathione S-transferase (GST)-Rac1 fusion protein was produced in strain DH5␣ of E. coli transformed with pGEX-2T-Rac1 and cleaved with thrombin (62). Recombinant Rac1 (1 g) was preloaded with [␥-33 P]GTP (2,000 to 4,000 Ci/mmol; NEN) in 25 l of loading buffer (20 mM Tris-HCl [pH 7.6], 25 mM NaCl, 0.1 mM dithiothreitol, 4 M GTP, 4 mM EDTA) for 10 min at 30°C (63).…”
Section: Methodsmentioning
confidence: 99%
“…It was shown previously that HGF-induced dissociation of MDCK epithelial cells is dependent on phosphatidylinositol 3-kinase (PI3K) activity (Potempa and Ridley, 1998). It was also suggested that whereas HGF-induced Ras activation increases Rac-GTP in a PI3K-dependent manner (Ridley et al, 1995;Scita et al, 1999;Royal et al, 2000;Zondag et al, 2000), RhoA might be activated through a PI3K-independent pathway (Zondag et al, 2000). In contrast to the latter report, we found that both RhoA ( Figure 7B) and Rac activation by HGF were strictly dependent on PI3K activity, being inhibited by treatment of the cultures with the PI3K inhibitor LY294002 (2 h, 20 M; Figure 7B).…”
Section: ⌬N-p120 Abrogates Activation Of Rhoa By Hgfmentioning
confidence: 99%
“…Growth factors like HGF, EGF, and PDGF have been shown to stimulate Rac (Ridley et al, 1995;Scita et al, 1999;Royal et al, 2000;Zondag et al, 2000) and RhoA activities (Zondag et al, 2000) both in fibroblasts and epithelial cells. Accordingly, HGF stimulation of control MDCK cells resulted in a rapid and transient increase (between 2 and 10 min after addition of the growth factor) of Rac-GTP (our unpublished results).…”
Section: ⌬N-p120 Abrogates Activation Of Rhoa By Hgfmentioning
confidence: 99%
“…The noncatalytic parts of the structurally complex GEFs link the exchange activity to cellular processes and inhibit the DH domain exchange activity (Zheng, 2001;Hoffman and Cerione, 2002). Cellular inputs, such as protein (Hart et al, 1998;Scita et al, 1999;Innocenti et al, 2002) and phospholipid binding to (Han et al, 1998;Nimnual et al, 1998;Crompton et al, 2000;Das et al, 2000;Russo et al, 2001), and phosphorylation of (Crespo et al, 1997;Han et al, 1997;Schuebel et al, 1998;Aghazadeh et al, 2000) these regulatory regions derepress exchange activity. Integration of cellular signals by Rho GEFs can focus GTPase activity to allow temporal and spatially localized activation of actin cytoskeletal rearrangements.…”
Section: Introductionmentioning
confidence: 99%